Effect of Impairment on the Prevalence and Comorbidities of Attention Deficit Hyperactivity Disorder in a National Survey: Nation-Wide Prevalence and Comorbidities of ADHD - ARMAN, AYŞE; PERDAHLI FİŞ, NEŞE (SAGE PUBLICATIONS INC, 2022)
Objective: This study aimed to determine the prevalence and comorbidities of attention-deficit hyperactivity disorder (ADHD) by evaluating a large-scale nation-wide sample of children. Method: The inclusion criterion was being enrolled as a 2nd, 3rd, or 4th-grade student. A semi-structured diagnostic interview (K-SADS-PL), DSM-IV-Based Screening Scale for Disruptive Behavior Disorders, and assessment of impairment (by both parents and teachers) were applied to 5,842 participants. Results: The prevalence of ADHD was 19.5% without impairment and 12.4% with impairment. Both ADHD with and without impairment groups had similar psychiatric comorbidity rates except for oppositional defiant disorder (ODD) and conduct disorder (CD) diagnoses. Impairment in the ADHD group resulted in significantly higher ODD and CD diagnoses. Conclusion: Even when impairment is not described, other psychiatric disorders accompany the diagnosis of ADHD and may cause impairment in the future. Impairment in the diagnosis of ADHD significantly increases the likelihood of ODD and CD.
Keywords: attention deficit hyperactivity disorder; prevalence; epidemiology; Turkey; MENTAL-DISORDERS; PSYCHIATRIC-DISORDERS; WORLDWIDE PREVALENCE; TURKISH CHILDREN; IV; OVERDIAGNOSIS; EPIDEMIOLOGY; RELIABILITY; SCHEDULE